The presence of Brecht’s theories in theater training and in the contemporary scene as a way to make violence visible - Rodríguez Herrera, Raúl Ángel Valentín (2023)
A good part of the study programs of the Degree in theater and/or acting are designed to train stage creators who, during their professional stage, will dedicate themselves to creating fictions built from dramatic texts of an Aristotelian nature. In these models, other ways of articulating stage creation are excluded. For this reason, the present work tries to give greater prominence to Brechtian ideas; with the purpose that the students assume their creation from a greater aesthetic, ethical and political conscience. The intention will be to promote tools so that students; as well as scenic creators and creators articulate artistic practices that denounce, criticize and/or make violence visible. It is pertinent that teachers assume other pedagogies according to the needs of our time, because we cannot continue replicating models of creation that have been surpassed by the march of history.